MEMAHAMI PENGALAMAN PROSES PENGAMBILAN KEPUTUSAN REMAJA BROKEN HOME DALAM ROMANTIC RELATIONSHIP - Haidar, Iqbal; Ratri R, Lintang; Dwiningtyas S, Hapsari (Interaksi Online, 2024)
The romantic lives of children whose parents are divorced are often challenging due to their traumatic experiences. Divorce can diminish children's self-confidence in romantic relationships, particularly affecting females more frequently. This study aims to understand the experiences of adolescents from broken homes in the process of making commitments in romantic relationships. The research methodology employed is qualitative, using interpretative phenomenological analysis as a paradigm to understand five adolescent females from broken homes due to their father's infidelity. The findings indicate that, while remaining open to romantic relationships, one informant avoids binding commitments. Adolescents from broken homes go through three stages in making commitment decisions: acquaintance, approach, and integration of values and information. Difficulty in trusting others is a significant factor, stemming from the trauma of parental infidelity. In the acquaintance stage, they search for information using three strategies and assess it to avoid their partner's deception, proceeding cautiously. In the approach stage, all five informants easily terminate a relationship when encountering incompatibility. Not all informants disclose their family backgrounds, and they share their experiences with significant others for validation. In the integration stage, unwritten rules are formed, resulting in two commitment styles: moderate and casual.